REFORMING THE BUREAUCRACY: A STUDY OF PUBLIC ADMINISTRATION REFORMS AND THEIR IMPACT ON CORRUPTION AND SERVICE QUALITY - Muhammad Nur; Haziq Idris; Rina Farah (Yayasan Adra Karima Hubbi, 2025)
Pervasive issues of corruption and inadequate service delivery remain significant challenges in public administration globally, undermining public trust and hindering development. While many nations have initiated comprehensive bureaucratic reforms, their efficacy requires rigorous empirical assessment. This study aims to analyze the impact of specific public administration reforms—focusing on transparency, accountability, and performance management—on levels of corruption and the quality of public service delivery. A mixed-methods approach was employed, combining quantitative analysis of panel data from 20 countries over a 10-year period with in-depth qualitative case studies of two reformed public agencies. The findings indicate that reforms implementing e-governance and open data policies have a statistically significant negative correlation with corruption. Performance-based management systems were strongly associated with improved service quality metrics. However, the case studies revealed that the success of these reforms is significantly mediated by strong political leadership and the capacity to overcome institutional resistance. The study concludes that while structural reforms are effective tools, their success is contingent upon a supportive political and institutional environment, suggesting a need for context-sensitive implementation.